Implementasi Penggunaan Zinc Cream Pada Asuhan Keperawatan Tn. M Untuk Mencegah Infeksi Dan Mempercepat Pertumbuhan Granulasi Pada Luka Kaki Diabetic Di Asri Wound Care Center Medan - Rostini; Lily Putri Marito; Rafika Nur Siregar (STIKES Columbia Asia Medan, 2025)
Diabetes mellitus is a chronic disorder that arises when the pancreas does not produce enough insulin or when the body cannot use the insulin it produces properly, diabetic ulcers also referred to as diabetic foot ulcers, are medical conditions characterized by chronic, non-healing, sunken ulcers with edema with clear boundaries. Wounds in diabetic patients occur due to partial or complete damage to the skin that extends to the tissue under the skin, tendons, muscles, bones, or joints that occur in a person suffering from diabetes mellitus. Wound care that is currently developing is modern wound care which has a better rate of development of diabetic wound repair compared to using conventional wound care. The use of dressings must be considered to maintain wound moisture balance, one of the dressings that can be used is zinc cream as a primary dressing. Purpose: To prevent infection and help accelerate granulation growth in diabetic foot wound patients using zinc cream. Methods: By means of data collection and observation using case studies and subjects in diabetic foot wound patients with nursing problems of skin / tissue integrity disorders. Results: After taking wound care measures using zinc cream primary dressing for 12 times in 6 weeks there is a BWAT value in the dorsum pedis area from 37 to 22 and in the planta pedis area from 39 to 24. Conclusion: Treatment using zinc cream as a primary dressing proved effective in accelerating the healing process of diabetic foot wounds.